COVID-19 and pregnancy outcomes: a retrospective study from a tertiary health care center of Uttarakhand, India - Upreti, Purnima; Godara, Punam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Information regarding the effects of COVID-19 on pregnancy outcomes evolved rapidly in the recent years. This study aims to present the outcomes in COVID-19 positive pregnant women. Methods: This retrospective cohort study was conducted in a tertiary health care center of Uttarakhand, India from April 2021 to June 2021. The maternal and neonatal data for the included cases were extracted from hospital records and appropriately analysed. Results: The positivity rate of COVID-19 among obstetric population was 7.9% by universal screening protocol. 55.2% participants were in the age group of 25-30 years. Gestation age at presentation ranged from 6 weeks to 41 weeks. 47.3% participants had pre-existing comorbidities. 26.4% study subjects had pregnancy related comorbidities, the most common being gestational diabetes mellitus (14.7%), followed by pre-eclampsia (8.8%). Only 21.1% participants were symptomatic at presentation. Most common presenting symptom was fever (87.5%) followed by breathlessness (62.5%). 7.5% required invasive ventilation and 10.5% cases required intensive care unit (ICU) admission and 76.5% participants underwent caesarean section which was done for obstetric indications only. 3.9% participants died due to COVID-related complications. Nearly 35% neonates were preterm, 29.4% had low birth weight and 24.1% needed neonatal intensive care unit (NICU) admission. Nasopharyngeal swab for COVID reverse transcriptase-polymerase chain reaction (RT-PCR) after 24 hours of birth was negative in all neonates. There were 10 (14.7%) stillbirths. Conclusions: COVID-19 in pregnancy was associated with higher risks of gestational diabetes mellitus, preeclampsia and higher rates of invasive ventilation, ICU admission, caesarean sections, maternal mortality specially in women with pre-existing comorbidities, stillbirths, preterm births and NICU admission.